Health Risk Assessment of Heavy Metals in Shallot, Bantul Regency - Cicik Oktasari Handayani; Edi Martono; Rika Harini (Universitas Airlangga, 2022)
Introduction: Shallots are one of the horticultural products in great demand by the public. Excessive heavy metal content in shallot will affect people's health who consume it. This study examines the health risks of the people who consume shallot products produced in Srigading Village. Methods: Determination of sampling locations was carried out by purposive sampling method on shallot cultivation land that was ready to harvest, as many as 30 points, in September 2021. Soil and shallot samples were tested for the heavy metal content of Pb, Cd, Co, and Ni. The public health risk assessment was analyzed by looking at the Transfer Factor (TF) value, daily intake, health risk index, hazard index, and cancer risk. Results and Discussion: The concentration of heavy metals in shallots is Pb 19.14 – 30.04 mg kg-1, Cd 1.03 – 2.21 mg kg-1, Co 8.58 – 15.08 ppm, and Ni 6.00 – 10.09 mg kg-1. The average value of Transfer Factor (TF) shows metal uptake by shallots with metal levels Cd (1.07) > Pb (1.03) > Ni (0.73) > Co (0.46). The average daily dose shows that the daily consumption in children is higher than the daily dose for adults. Conclusion: Children are more at risk of being exposed to heavy metals compared to adults in consuming shallots based on the hazard index value. The continuous use of chemical fertilizers and chemical pesticides in shallot farming must be controlled to prevent the increase of accumulation of heavy metals in land and agricultural products.